Management of prostate cancer in Asia: Resource-stratified guidelines from the Asian Oncology Summit 2013 - Scott Williams (2018)
Many local and systemic options for prostate cancer have emerged in recent years, but existing management guidelines do not account for diversity in health resources between different countries. We present recommendations for the management of prostate cancer, stratified according to the extent of resource availability-based on a four-tier system of basic, limited, enhanced, and maximum resources-to enable applicability to Asian countries with differing levels of health-care resources. This statement of recommendations was formulated by a multidisciplinary panel from Asia-Pacific countries, at a consensus session on prostate cancer that was held as part of the 2013 Asian Oncology Summit in Bangkok, Thailand. © 2013 Elsevier Ltd.